The Muslim world after 9/11 - Rabasa, Angel (RAND, 2004)
Momentous events since September 11, 2001-Operation Enduring Freedom, the global war on terrorism, and the war in Iraq-have dramatically altered the political environment of the Muslim world. Many of the forces influencing this environment, however, are the products of trends that have been at work for many decades. This book examines the major dynamics that drive changes in the religio-political landscape of the Muslim world-a vast and diverse region that stretches from Western Africa through the Middle East to the Southern Philippines and includes Muslim communities and diasporas throughout.